Multi-modal deformation sensing hydrogel as well as preparation method and application thereof

By polymerizing sodium alginate with hyaluronic acid methacrylate in hydrogel, a multimodal deformation sensing hydrogel with self-templated hierarchical structure and orientation holes is solved, the three-dimensional mechanical changes of traditional hydrogels are solved. The problem of insufficient response capability has achieved the improvement of high response sensitivity and comprehensive mechanical performance, and is suitable for wearable intelligent sensors.

CN119264471AActive Publication Date: 2025-01-07SHANGHAI JIAOTONG UNIV

Patent Information

Application Number
CN202411601779.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-01-07
Estimated Expiration
2044-11-11

AI Technical Summary

Technical Problem

The application of existing hydrogels in identifying complex multi-strain environments is limited, especially traditional flexible sensors can only output a single signal, and have insufficient response capabilities in three-dimensional mechanical changes, so they cannot accurately capture mechanical signals of complex human behavior.

Method used

By polymerizing sodium alginate with hyaluronic acid methacrylate under oxygen-free and heat-induced conditions, a multimodal deformation sensing hydrogel has a highly aligned self-template hierarchy and orientation holes, three-dimensional strain detection is achieved and high response sensitivity.

Benefits of technology

The prepared multimodal deformation sensing hydrogel has excellent comprehensive mechanical properties and conductivity, and can detect complex behavior patterns within the three-dimensional strain range, providing high signal repeatability and high response sensitivity, suitable for wearable intelligent sensors Development.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119264471A_ABST
    Figure CN119264471A_ABST
Patent Text Reader

Abstract

The invention relates to a multi-mode deformation sensing hydrogel as well as a preparation method and application thereof. The sensing hydrogel comprises the following components: alginic acid hydrogel and methacrylic acid hyaluronic acid, and clamping two long ends of the alginic acid hydrogel, drying, dissolving methacrylic acid hyaluronic acid in water, and polymerizing and molding with the alginic acid hydrogel to obtain the multi-mode deformation sensing hydrogel. Compared with the prior art, the three-dimensional strain sensor has excellent comprehensive mechanical properties and conductivity, and has a three-dimensional strain detection range, good signal repeatability and high response sensitivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of gel production, and relates to a multi-modal deformation sensing hydrogel and a preparation method and application thereof. Background Art

[0002] In recent years, flexible electronic products have attracted widespread attention due to their ability to accurately record mechanical signals and monitor health and motion status in real time. Hydrogels are considered to be one of the promising materials for the development of smart flexible wearable devices due to their advantages such as simple preparation process, good biocompatibility, environmental friendliness and conductivity. However, the isotropic structural characteristics of hydrogels limit their application potential in identifying complex multi-strain environments. Nature has provided a lot of inspiration for the development of flexible wearable devices. Many soft tissues of organisms, such as skin and muscles, have highly ordered anisotropic microstructures that can actively sense and manage their own movements, showing high information response capabilities and contraction capabilities. At present, there are many hydrogel sensors that simulate the anisotropic structure of natural materials, which have been proven to effectively improve the sensing properties of hydrogels.

[0003] The 3D highly ordered structure improves the strength and mechanical fatigue resistance of the hydrogel, enhances the directional transfer of ions, and achieves precise and wide-range mechanical response. More importantly, the anisotropic morphology and multi-level structure lead to the asymmetry and directional selectivity of the hydrogel sensing performance, showing super-strong wide-range response ability and high sensitivity parallel to the orientation direction, and can respond quickly to mechanical changes in the vertical direction. This solves the defect that traditional flexible sensors can only output a single signal to a certain extent, but the effectiveness of flexible sensors is still subject to many challenges, including the limitation of unidirectional deformation and the limitation of two-dimensional mechanical response range. In fact, human behavior exhibits complex strain patterns. For example, when bending the wrist, walking, etc., tensile strain and compressive strain often interweave or occur simultaneously. Flexible sensors need to have the ability to respond to three-dimensional mechanical changes in order to accurately capture biological signals.

[0004] Therefore, it is of great significance to develop a hydrogel material with a structure close to human tissue, good mechanical properties, and the ability to sensitively and stably respond to three-dimensional mechanical stimulation.

[0005] Patent CN118206799A discloses a method for preparing anisotropic hydrogels containing porous open channels, wherein natural polymer sodium alginate and silver nanowires are induced to form a long-range ordered layered structure by bidirectional freezing, and a poly(N-isopropylacrylamide) hydrogel doped with carbon nanotubes is polymerized in a two-stage in-situ manner by unidirectional freezing in the anisotropic layered framework. Although the patent adopts an anisotropic structure, the anisotropic layered structure is composed of aerogel materials, which has poor mechanical strength and flexibility; although the patent forms honeycomb holes by unidirectional freezing-assisted method, these holes are not anisotropic and their size is difficult to control.

[0006] Patent CN116333379A discloses a multifunctional ionic hydrogel, strain sensor and flexible all-solid-state supercapacitor and its preparation method and application. The preparation steps include: dissolving trehalose in deionized water and stirring to prepare a uniform trehalose solution; adding anhydrous lithium chloride to the trehalose solution and stirring to prepare a lithium chloride / trehalose mixed solution; taking the lithium chloride / trehalose mixed solution, adding acrylamide, acrylic acid, N,N′-methylenebisacrylamide and 2-hydroxy-4′-(2-hydroxyethoxy)-2-methylphenylpropiophenone to the mixed solution, and stirring vigorously until a transparent uniform solution is formed; pouring the mixed solution into a silicone mold, and then polymerizing under ultraviolet light to form an ionic hydrogel. However, the preparation method of this patent is simple and the hydrogel structure cannot be customized; the photopolymerization method used in this patent uses a large amount of initiator, which increases the toxicity of the hydrogel and makes the hydrogel have potential risks in the application of wearable smart devices; at the same time, the sensing characteristics of the hydrogel in this patent are only reflected in the tensile strain, and the response sensitivity is low in a small strain range.

[0007] Patent CN113461974A discloses a gas-responsive surface lubricating hydrogel and its preparation method, which coordinates the covalent polymerization network and the gas-responsive supramolecular network system, wherein the covalent polymer network skeleton can provide a certain mechanical basis, has a porous structure, and is conducive to the movement of the supramolecular system in a three-dimensional network; at the same time, the supramolecular components with gas response can undergo a reversible gel-sol transition under the action of carbon dioxide and nitrogen. However, the preparation method of methacryloyl hyaluronic acid in this patent is relatively complicated, has high reaction requirements, increases costs, and may introduce impurities into the product; and in this patent, methacryloyl hyaluronic acid is used as a cross-linking agent to form an interpenetrating network covalent skeleton with a single network hydrogel, which has limited improvement in mechanical properties. Summary of the invention

[0008] The purpose of the present invention is to provide a multimodal deformation sensing hydrogel and its preparation method and application in order to overcome at least one defect of the above-mentioned prior art. The present invention has excellent comprehensive mechanical properties and conductive properties, a three-dimensional strain detection range, good signal repeatability and high response sensitivity.

[0009] The purpose of the present invention can be achieved by the following technical solutions:

[0010] One of the technical solutions of the present invention is to provide a multimodal deformation sensing hydrogel, which comprises the following components in parts by weight:

[0011] 1-3 parts of alginate hydrogel and 1-3 parts of methacrylated hyaluronic acid;

[0012] The two long ends of the alginate hydrogel were clamped and dried, and methacrylate hyaluronic acid was dissolved in water and polymerized with the alginate hydrogel to obtain a multimodal deformation sensing hydrogel.

[0013] Furthermore, the alginate hydrogel is placed in air to dry at a temperature of 10-40° C. for 3-6 hours.

[0014] Furthermore, methacrylate hyaluronic acid and alginate hydrogel are polymerized under anaerobic and heat-induced conditions, the polymerization temperature is 40-60° C., and the time is 3-6 hours.

[0015] One of the technical solutions of the present invention is to provide a method for preparing the multimodal deformation sensing hydrogel, the method comprising the following steps:

[0016] S1. adding sodium alginate into water to dissolve to obtain a sodium alginate solution, pouring the sodium alginate solution into a mold, adding a metal ion solution to react to obtain an alginate hydrogel, clamping the two long ends of the alginate hydrogel, and drying to induce a spontaneous mechanical signal to create a hydrogel with a highly aligned self-templated hierarchical structure;

[0017] S2, adding hyaluronic acid into water to dissolve, adding glycidyl methacrylate, triethylamine and tetrabutylammonium bromide to react, and obtaining methacrylate hyaluronic acid;

[0018] S3. Add methacrylated hyaluronic acid into water to dissolve it, add a cross-linking agent and an initiator to mix, inject the mixed solution into a mold, and polymerize it with alginate hydrogel to form it. Under the action of the redox initiation system, the methacrylated hyaluronic acid molecules are cross-linked with each other through free radical reactions, and the fiber structure is used as a template to induce the formation of oriented holes. At the same time, the methacrylated hyaluronic acid and the alginate hydrogel are tightly combined through hydrogen bonds to obtain a multimodal deformation sensing hydrogel.

[0019] Furthermore, in step S1, the mass / volume ratio of sodium alginate to water is (1-2 g):(25-30 mL),

[0020] The metal ion solution is selected from one or more of a calcium chloride solution, a zinc chloride solution, and a barium chloride solution, and the concentration of the metal ion solution is 0.05 to 0.1 g / mL.

[0021] The volume ratio of the sodium alginate solution to the metal ion solution is (1-2):(1-3).

[0022] Furthermore, the dissolution temperature in step S1 is 10 to 40°C and the dissolution time is 8 to 12 hours.

[0023] The reaction temperature is 10-40°C and the reaction time is 3-6 hours.

[0024] Furthermore, in step S2, the mass / volume ratio of hyaluronic acid to water is (1-3 g):(50-60 mL),

[0025] The mass / volume ratio of hyaluronic acid, glycidyl methacrylate, triethylamine and tetrabutylammonium bromide is (45-50 g):(1-8 mL):(1-8 mL):(1-8 g).

[0026] Furthermore, the dissolution temperature in step S2 is 10 to 40°C and the dissolution time is 3 to 6 hours.

[0027] The reaction temperature is 40-60°C and the reaction time is 1-4 hours.

[0028] As a preferred technical solution, in step S2, the reaction is cooled to room temperature, and the reaction solution is precipitated, washed, and freeze-dried.

[0029] As a preferred technical solution, the product is precipitated and washed in acetone.

[0030] As a preferred technical solution, the freeze-drying temperature is -110 to -90°C and the time is 12 to 24 hours.

[0031] Furthermore, in step S3, the mass / volume ratio of methacrylate hyaluronic acid to water is (0.02-0.04 g): 1 mL,

[0032] The crosslinking agent is selected from one or more of polyethylene glycol diacrylate, N,N-methylenebisacrylamide, cyclotriene bond, and triallyl isocyanurate; the initiator is selected from one or more of ammonium persulfate, potassium persulfate, 2-hydroxy-2-methylpropiophenone, and α-ketoglutaric acid; the mass ratio of methacrylic hyaluronic acid, crosslinking agent, and initiator is 1:(0.001-0.002):(0.002-0.003);

[0033] The dissolution temperature is 10-40°C and the dissolution time is 1-2 hours.

[0034] The mixing temperature is 10-40°C and the mixing time is 10-20 minutes.

[0035] One of the technical solutions of the present invention is to provide an application of the multimodal deformation sensing hydrogel, wherein the sensing hydrogel is applied to a wearable flexible sensor.

[0036] Compared with the prior art, the present invention has the following beneficial effects:

[0037] (1) The present invention induces spontaneous mechanical signals to create a hydrogel with a highly aligned self-templated hierarchical structure; the long end of the alginate hydrogel is clamped and fixed with a bracket and exposed to air for drying; the mechanical signal causes the ionic interaction of the alginate hydrogel to be sacrificed, and the polymer chains are arranged along the stress direction to form a hierarchical fiber structure; at the same time, under the action of the redox initiation system, methacrylate hyaluronic acid is cross-linked with each other through free radical reactions, and the fiber structure is used as a template to induce the formation of oriented holes; inspired by peripheral nerves with multi-layer ordered structures and impulse conduction using ionic signals, a hydrogel with a multi-layer sandwich structure consisting of anisotropic fibers-holes-fibers is innovatively prepared, and the preparation method is simple and effective, low-cost, and has the prospect of industrial implementation;

[0038] (2) The sensing hydrogel prepared by the present invention has excellent comprehensive mechanical properties and conductive properties, which lays a good foundation for the development of wearable smart sensors and has great potential in flexible electronic applications such as sports science and health diagnosis;

[0039] (3) The preparation process adopted in the present invention obtains a multimodal deformation sensing hydrogel with a highly anisotropic structure having a three-dimensional strain detection range, good signal repeatability and high response sensitivity, which can be used to prepare a multifunctional system that can sense three-dimensional mechanical changes and accurately identify complex behavior patterns, and has broad practical value. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 is the nuclear magnetic resonance spectrum of hyaluronic acid and methacrylic hyaluronic acid in Example 1 of the present invention;

[0041] Figure 2 Total reflection infrared absorption spectra (ATR-FTIR) of calcium alginate hydrogel, methacrylate hyaluronic acid and multimodal deformation sensing hydrogel in Example 1 of the present invention;

[0042] Figure 3 This is a scanning electron microscope (SEM) image of the multimodal deformation sensing hydrogel fiber structure in Example 1 of the present invention;

[0043] Figure 4 This is a SEM image of the pore structure of the multimodal deformation sensing hydrogel in Example 1 of the present invention;

[0044] Figure 5 is a SEM image of a cross section of the multimodal deformation sensing hydrogel in Example 1 of the present invention;

[0045] Figure 6 This is a diagram showing the sensing performance of the multi-modal deformation sensing hydrogel subjected to tensile strain in Example 1 of the present invention;

[0046] Figure 7 This is a sensing performance diagram of the multi-modal deformation sensing hydrogel subjected to compressive strain in Example 1 of the present invention;

[0047] Figure 8 This is a sensing performance diagram of the multimodal deformation sensing hydrogel fixed to the heel of walking in Example 1 of the present invention;

[0048] Fig. 9 This is a sensing performance diagram of the multimodal deformation sensing hydrogel fixed to the ball of the toe while walking in Example 1 of the present invention;

[0049] Fig.10 This is a diagram showing the sensing performance of the multimodal deformation sensing hydrogel fixed to the heel during walking, running and jumping in Example 1 of the present invention. DETAILED DESCRIPTION

[0050] The present invention is described in detail below in conjunction with specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and a specific operation process, but the protection scope of the present invention is not limited to the following embodiments.

[0051] Unless otherwise specified, the equipment used in the following examples are all conventional equipment in the art; the reagents used are all commercially available products or prepared by conventional methods in the art unless otherwise specified. Anything not described in detail in the following examples can be achieved by conventional experimental means in the art.

[0052] The mechanical properties, conductive properties, and sensing properties of the multimodal deformation sensing hydrogel prepared in this example were characterized using an LD23 503 universal tensile testing machine, a Biologic VMP-3 electrochemical workstation, and a Keithley 2450 source meter.

[0053] Embodiment 1:

[0054] A multimodal deformation sensing hydrogel and a preparation method thereof, the specific steps are as follows:

[0055] S1. Preparation of calcium alginate hydrogel.

[0056] 0.2 g of sodium alginate was added to 5 mL of deionized water, and the mixture was stirred and dissolved at room temperature for 10 h to obtain a sodium alginate solution. 0.4 g of calcium chloride was dissolved in 5 mL of deionized water, and 5 mL of the prepared sodium alginate solution was poured into a mold. 5 mL of calcium chloride solution was injected from above and reacted at room temperature for 4 h to obtain a calcium alginate hydrogel (AlgCa). The two long ends of the calcium alginate hydrogel were clamped with a bracket and placed in air and dried at room temperature for 4 h.

[0057] S2. Preparation of methacrylated hyaluronic acid,

[0058] 0.1 g of hyaluronic acid (HA) was added to 5 mL of deionized water, and the mixture was dissolved by stirring at room temperature for 4 h. 0.015 mL of glycidyl methacrylate, 0.015 mL of triethylamine and 0.015 g of tetrabutylammonium bromide were added, and the mixture was reacted at 50 ° C for 2 h. After cooling to room temperature, the reaction solution was precipitated and washed in acetone, and freeze-dried at -110 ° C for 12 h to obtain methacrylate hyaluronic acid (GMHA).

[0059] like Figure 1 As shown, the nuclear magnetic resonance spectrum shows that, relative to hyaluronic acid, the methacrylic acid hyaluronic acid prepared in this example has two new proton peaks caused by methacrylate groups at 5.22ppm and 5.50ppm;

[0060] like Figure 2 As shown in the total reflection infrared absorption spectrum (ATR-FTIR), compared with calcium alginate hydrogel (AlgCa), the methacrylate hyaluronic acid prepared in this example has a higher peak at 1375 cm -1 and 1153cm -1 There is an obvious characteristic peak at the carbon-carbon double bond (RC=CH 2 ) caused by functional groups;

[0061] The test results of nuclear magnetic resonance spectrum and total reflection infrared absorption spectrum prove that the methacrylate hyaluronic acid in this embodiment is successfully synthesized;

[0062] S3. Preparation of multimodal deformation sensing hydrogels.

[0063] 0.1 g of methacrylated hyaluronic acid was added to 4 mL of deionized water, and the mixture was dissolved by stirring at room temperature for 1 h. 0.0001 g of N,N-methylenebisacrylamide and 0.0002 g of ammonium persulfate were added, and the mixture was mixed by stirring at room temperature for 10 min. The mixed solution was injected into a mold, and polymerized with 0.15 g of calcium alginate hydrogel under anaerobic conditions at 40 °C for 3 h to obtain a multimodal deformation sensing hydrogel (AMH).

[0064] The performance of the above sensing hydrogel was tested, and the specific results are as follows:

[0065] T1. Total reflection infrared absorption spectrum test results of materials.

[0066] like Figure 2 As shown in the figure, the total reflection infrared absorption spectrum shows that cross-linking reaction occurs between methacrylate hyaluronic acid molecules, and the carbon-carbon double bond is destroyed in this process, which is reflected in the spectrum as the multimodal deformation sensing hydrogel in this embodiment is located at 1375cm -1 and 1153cm -1 The absorption band representing the presence of double bonds disappears;

[0067] Further observation shows that the spectrum of methacrylated hyaluronic acid is between 3640 and 2980 cm -1 A broad absorption peak appears in the region, which is attributed to the -OH and -NH groups in the molecule participating in the formation of intramolecular and intermolecular hydrogen bonds, leading to the enhancement of stretching vibration;

[0068] In contrast, calcium alginate hydrogels have a lot of -OH and -COOH groups that bind to Ca 2+ A stable chelating structure is formed, which weakens the performance of these groups in the spectrum and makes the corresponding absorption peaks difficult to observe;

[0069] At the same position, a broad peak was observed in the multimodal deformation sensing hydrogel, proving that the multimodal deformation sensing hydrogel was successfully synthesized in this embodiment;

[0070] T2, Scanning electron microscope (SEM) test results of materials,

[0071] like Figure 3 As shown, fibers arranged along the axial direction were observed in the multimodal deformation sensing hydrogel prepared in this embodiment. Through in-situ clamping, the calcium alginate hydrogel formed a thick fiber structure arranged along the axial direction, and each ultrafine fiber was submicron in size.

[0072] like Figure 4 As shown, an oriented porous structure was observed in the multimodal deformation sensing hydrogel prepared in this embodiment. The methacrylate hyaluronic acid used the oriented fiber structure as a template, and the holes grew along the fibers. The pore walls were parallel to the fiber arrangement direction, forming oriented holes.

[0073] like Figure 5 As shown, the multimodal deformation sensing hydrogel prepared in this embodiment presents a multilayer sandwich structure of fiber-pore-fiber, indicating that the multimodal deformation sensing hydrogel prepared in this embodiment is composed of oriented fibers and oriented pores;

[0074] T3. Mechanical properties test results of materials,

[0075] The mechanical properties data of the above sensing hydrogels are shown in Table 1;

[0076] Table 1 Mechanical properties data of multimodal deformation sensing hydrogel in the embodiment

[0077] Example Maximum tensile elongation Maximum tensile strength (MPa) Maximum compressive strength (MPa) 1 102% 1.51 3.5 2 93% 1.64 2.9 3 86% 1.25 2.3 4 135% 1.34 2.5 5 115% 1.44 3.2 6 121% 1.27 2.9

[0078] As shown in Table 1, the tensile results show that the multimodal deformation sensing hydrogel prepared in this embodiment has a maximum tensile elongation of 102% and a maximum tensile strength of 1.51 MPa;

[0079] The compression results show that when the multimodal deformation sensing hydrogel prepared in this embodiment is compressed to 70%, the maximum compressive strength reaches 3.5 MPa;

[0080] It shows that the multimodal deformation sensing hydrogel prepared in this example has excellent tensile and compressive mechanical properties;

[0081] T4. Test results of the conductivity of materials.

[0082] The conductivity performance data of the above sensing hydrogel are shown in Table 2;

[0083] Table 2 Conductive performance data of multimodal deformation sensing hydrogel in the embodiment

[0084] Example 1 2 3 4 5 6 Conductivity (S / cm) 0.044 0.031 0.036 0.027 0.04 0.035

[0085] As shown in Table 2, the conductivity of the multimodal deformation sensing hydrogel prepared in this embodiment is 0.044 S / cm, indicating that the multimodal deformation sensing hydrogel prepared in this embodiment has excellent conductive properties;

[0086] T5. Material sensing performance test results,

[0087] like Figure 6 As shown, the relative resistance change of the multimodal deformation sensing hydrogel prepared in this embodiment under different tensile strains (1%, 2%, 5%, 10% and 20%) increases continuously with the increase of tensile strain, indicating that the multimodal deformation sensing hydrogel prepared in this embodiment can convert tensile deformation into a stable electrical signal and exhibits good mechanical responsiveness;

[0088] like Figure 7 As shown, the relative resistance change of the multimodal deformation sensing hydrogel prepared in this embodiment under different compressive strains (1%, 2%, 5%, 10% and 20%) decreases continuously with the increase of compressive strain, indicating that the multimodal deformation sensing hydrogel prepared in this embodiment can convert compressive deformation into a stable electrical signal, showing good mechanical responsiveness;

[0089] The material was fixed on the heel of subjects with medium arches and they walked;

[0090] like Figure 8 As shown, during walking, when the heel is put down, the pressure will increase to the maximum value, and the whole foot is placed on the ground, and the heel is lifted up to continue moving forward, and the pressure gradually decreases to zero. The relative resistance of the multimodal deformation sensing hydrogel prepared in this embodiment changes regularly during the walking process;

[0091] The material was fixed on the ball of the toes of subjects with medium arches and walking activities were performed;

[0092] like Fig. 9 As shown, during walking, after the ball of the toe is placed on the floor, the heel is slowly lifted, and the pressure on the ball of the toe increases to the maximum value. Then, the toe is lifted and the pressure gradually decreases to zero. The relative resistance of the multimodal deformation sensing hydrogel prepared in this embodiment changes regularly during the walking process.

[0093] During walking, due to the difference in force, there are obvious differences in peak current, peak shape and interval time between the heel and the ball of the toe, which shows that the multimodal deformation sensing hydrogel prepared in this example has a three-dimensional sensing range and the ability to distinguish plantar pressure points;

[0094] The material was fixed on the heel of subjects with medium arches and they performed walking, running and jumping activities.

[0095] like Fig.10 As shown, the sensing signals of the multimodal deformation sensing hydrogel prepared in this embodiment are significantly different in each sports scene. During walking, the peak width is large, showing the characteristics of a wide peak. The running and jumping movements are faster and the force is more concentrated, so the peak width is continuously reduced and the peak shape is sharper.

[0096] High-speed motion will produce faster mechanical impact, resulting in a harsher environment for sensing response. However, the multimodal deformation sensing hydrogel prepared in this embodiment accurately and stably completes the sensing response.

[0097] The special three-dimensional response ability of the multimodal deformation sensing hydrogel prepared in this embodiment allows different movement modes to generate different current signals. The movement mode, movement frequency and force area of ​​the human body can be quickly and accurately determined through different electrical signal waveforms. It is a promising candidate in the fields of sports science, infant health and rehabilitation training.

[0098] Embodiment 2:

[0099] A multimodal deformation sensing hydrogel and a preparation method thereof, the specific steps are as follows:

[0100] S1. Preparation of calcium alginate hydrogel.

[0101] 0.5 g of sodium alginate was added to 10 mL of deionized water, and the mixture was stirred and dissolved at room temperature for 12 h to obtain a sodium alginate solution. 0.5 g of calcium chloride was dissolved in 10 mL of deionized water, and 10 mL of the prepared sodium alginate solution was poured into a mold. 10 mL of calcium chloride solution was injected from above and reacted at room temperature for 4 h to obtain a calcium alginate hydrogel. The two long ends of the calcium alginate hydrogel were clamped with a bracket and placed in the air and dried at room temperature for 4 h.

[0102] S2. Preparation of methacrylated hyaluronic acid,

[0103] 0.2 g of hyaluronic acid was added to 8 mL of deionized water, and the mixture was dissolved by stirring at room temperature for 4 h. 0.03 mL of glycidyl methacrylate, 0.03 mL of triethylamine and 0.03 g of tetrabutylammonium bromide were added, and the mixture was reacted at 50°C for 4 h. After cooling to room temperature, the reaction solution was precipitated and washed in acetone, and freeze-dried at -100°C for 24 h to obtain methacrylated hyaluronic acid.

[0104] S3. Preparation of multimodal deformation sensing hydrogels.

[0105] 0.15 g of methacrylated hyaluronic acid was added to 4 mL of deionized water, and the mixture was dissolved by stirring at room temperature for 2 h. 0.00015 g of N,N-methylenebisacrylamide and 0.0003 g of ammonium persulfate were added, and the mixture was mixed by stirring at room temperature for 15 min. The mixed solution was injected into a mold, and polymerized with 0.3 g of calcium alginate hydrogel under anaerobic conditions at 45 °C for 3 h to obtain a multimodal deformation sensing hydrogel.

[0106] As shown in Table 1, the tensile results show that the multimodal deformation sensing hydrogel prepared in this embodiment has a maximum tensile elongation of 93% and a maximum tensile strength of 1.64 MPa;

[0107] The compression results show that when the multimodal deformation sensing hydrogel prepared in this embodiment is compressed to 70%, the maximum compressive strength reaches 2.9 MPa;

[0108] It shows that the multimodal deformation sensing hydrogel prepared in this example has excellent tensile and compressive mechanical properties;

[0109] As shown in Table 2, the conductivity of the multimodal deformation sensing hydrogel prepared in this example is 0.031 S / cm, indicating that the multimodal deformation sensing hydrogel prepared in this example has excellent conductive properties.

[0110] Embodiment 3:

[0111] A multimodal deformation sensing hydrogel and a preparation method thereof, the specific steps are as follows:

[0112] S1. Preparation of calcium alginate hydrogel.

[0113] 2 g of sodium alginate was added to 50 mL of deionized water, and the mixture was stirred and dissolved at room temperature for 10 h to obtain a sodium alginate solution. 6 g of calcium chloride was dissolved in 100 mL of deionized water, and 50 mL of the prepared sodium alginate solution was poured into a mold. 100 mL of calcium chloride solution was injected from above and reacted at room temperature for 3 h to obtain a calcium alginate hydrogel. The two long ends of the calcium alginate hydrogel were clamped with a bracket and placed in the air and dried at room temperature for 4 h.

[0114] S2. Preparation of methacrylated hyaluronic acid,

[0115] 1.5 g of hyaluronic acid was added to 50 mL of deionized water, and the mixture was stirred and dissolved at room temperature for 3 h. 0.2 mL of glycidyl methacrylate, 0.2 mL of triethylamine and 0.2 g of tetrabutylammonium bromide were added, and the mixture was reacted at 52° C. for 3 h. After cooling to room temperature, the reacted solution was precipitated and washed in acetone, and freeze-dried at -95° C. for 24 h to obtain methacrylated hyaluronic acid.

[0116] S3. Preparation of multimodal deformation sensing hydrogels.

[0117] 1.5 g of methacrylated hyaluronic acid was added to 50 mL of deionized water, and the mixture was dissolved by stirring at room temperature for 2 h. 0.0015 g of N,N-methylenebisacrylamide and 0.0045 g of potassium persulfate were added, and the mixture was mixed by stirring at room temperature for 10 min. The mixed solution was injected into a mold, and polymerized with 2 g of calcium alginate hydrogel under anaerobic conditions at 50 °C for 5 h to obtain a multimodal deformation sensing hydrogel.

[0118] As shown in Table 1, the tensile results show that the multimodal deformation sensing hydrogel prepared in this embodiment has a maximum tensile elongation of 86% and a maximum tensile strength of 1.25 MPa;

[0119] The compression results show that when the multimodal deformation sensing hydrogel prepared in this embodiment is compressed to 70%, the maximum compressive strength reaches 2.3 MPa;

[0120] It shows that the multimodal deformation sensing hydrogel prepared in this example has excellent tensile and compressive mechanical properties;

[0121] As shown in Table 2, the conductivity of the multimodal deformation sensing hydrogel prepared in this example is 0.036 S / cm, indicating that the multimodal deformation sensing hydrogel prepared in this example has excellent conductive properties.

[0122] Embodiment 4:

[0123] A multimodal deformation sensing hydrogel and a preparation method thereof, the specific steps are as follows:

[0124] S1. Preparation of calcium alginate hydrogel.

[0125] 0.5 g of sodium alginate was added to 10 mL of deionized water, and the mixture was stirred and dissolved at room temperature for 12 h to obtain a sodium alginate solution. 0.8 g of calcium chloride was dissolved in 10 mL of deionized water, and 10 mL of the prepared sodium alginate solution was poured into a mold. 10 mL of calcium chloride solution was injected from above and reacted at room temperature for 5 h to obtain a calcium alginate hydrogel. The two long ends of the calcium alginate hydrogel were clamped with a bracket and placed in the air and dried at room temperature for 5 h.

[0126] S2. Preparation of methacrylated hyaluronic acid,

[0127] 0.2 g of hyaluronic acid was added to 10 mL of deionized water, and the mixture was stirred and dissolved at room temperature for 4 h. 0.03 mL of glycidyl methacrylate, 0.03 mL of triethylamine and 0.03 g of tetrabutylammonium bromide were added, and the mixture was reacted at 50° C. for 3 h. After cooling to room temperature, the reacted solution was precipitated and washed in acetone, and freeze-dried at -110° C. for 18 h to obtain methacrylated hyaluronic acid.

[0128] S3. Preparation of multimodal deformation sensing hydrogels.

[0129] 0.2 g of methacrylated hyaluronic acid was added to 10 mL of deionized water, and the mixture was dissolved by stirring at room temperature for 1 h. 0.00025 g of N,N-methylenebisacrylamide and 0.00055 g of potassium persulfate were added, and the mixture was mixed by stirring at room temperature for 10 min. The mixed solution was injected into a mold, and polymerized with 0.5 g of calcium alginate hydrogel under anaerobic conditions at 40 °C for 6 h to obtain a multimodal deformation sensing hydrogel.

[0130] As shown in Table 1, the tensile results show that the multimodal deformation sensing hydrogel prepared in this embodiment has a maximum tensile elongation of 135% and a maximum tensile strength of 1.34 MPa;

[0131] The compression results show that when the multimodal deformation sensing hydrogel prepared in this embodiment is compressed to 70%, the maximum compressive strength reaches 2.5 MPa;

[0132] It shows that the multimodal deformation sensing hydrogel prepared in this example has excellent tensile and compressive mechanical properties;

[0133] As shown in Table 2, the conductivity of the multimodal deformation sensing hydrogel prepared in this example is 0.027 S / cm, indicating that the multimodal deformation sensing hydrogel prepared in this example has excellent conductive properties.

[0134] Embodiment 5:

[0135] A multimodal deformation sensing hydrogel and a preparation method thereof, the specific steps are as follows:

[0136] S1. Preparation of calcium alginate hydrogel.

[0137] 3 g of sodium alginate was added to 50 mL of deionized water, and the mixture was stirred and dissolved at room temperature for 8 h to obtain a sodium alginate solution. 2 g of calcium chloride was dissolved in 50 mL of deionized water, and 50 mL of the prepared sodium alginate solution was poured into a mold. 50 mL of calcium chloride solution was injected from above and reacted at room temperature for 5 h to obtain a calcium alginate hydrogel. The two long ends of the calcium alginate hydrogel were clamped with a bracket and placed in the air and dried at room temperature for 6 h.

[0138] S2. Preparation of methacrylated hyaluronic acid,

[0139] 2 g of hyaluronic acid was added to 50 mL of deionized water, and the mixture was stirred and dissolved at room temperature for 4 h. 0.2 mL of glycidyl methacrylate, 0.2 mL of triethylamine and 0.2 g of tetrabutylammonium bromide were added, and the mixture was reacted at 50°C for 4 h. After cooling to room temperature, the reaction solution was precipitated and washed in acetone, and freeze-dried at -100°C for 24 h to obtain methacrylated hyaluronic acid.

[0140] S3. Preparation of multimodal deformation sensing hydrogels.

[0141] 2 g of methacrylated hyaluronic acid was added to 50 mL of deionized water, and the mixture was dissolved by stirring at room temperature for 2 h. 0.002 g of N,N-methylenebisacrylamide and 0.004 g of ammonium persulfate were added, and the mixture was stirred at room temperature for 15 min. The mixed solution was injected into a mold, and polymerized with 3 g of calcium alginate hydrogel under anaerobic conditions at 45 °C for 6 h to obtain a multimodal deformation sensing hydrogel.

[0142] As shown in Table 1, the tensile results show that the multimodal deformation sensing hydrogel prepared in this embodiment has a maximum tensile elongation of 115% and a maximum tensile strength of 1.44 MPa;

[0143] The compression results show that when the multimodal deformation sensing hydrogel prepared in this embodiment is compressed to 70%, the maximum compressive strength reaches 3.2 MPa;

[0144] It shows that the multimodal deformation sensing hydrogel prepared in this example has excellent tensile and compressive mechanical properties;

[0145] As shown in Table 2, the conductivity of the multimodal deformation sensing hydrogel prepared in this example is 0.04 S / cm, indicating that the multimodal deformation sensing hydrogel prepared in this example has excellent conductive properties.

[0146] Embodiment 6:

[0147] A multimodal deformation sensing hydrogel and a preparation method thereof, the specific steps are as follows:

[0148] S1. Preparation of calcium alginate hydrogel.

[0149] 0.5 g of sodium alginate was added to 10 mL of deionized water, and the mixture was stirred and dissolved at room temperature for 8 h to obtain a sodium alginate solution. 0.4 g of calcium chloride was dissolved in 8 mL of deionized water, and 10 mL of the prepared sodium alginate solution was poured into a mold. 8 mL of calcium chloride solution was injected from above and reacted at room temperature for 5 h to obtain a calcium alginate hydrogel. The two long ends of the calcium alginate hydrogel were clamped with a bracket and placed in the air and dried at room temperature for 4 h.

[0150] S2. Preparation of methacrylated hyaluronic acid,

[0151] 0.4 g of hyaluronic acid was added to 10 mL of deionized water, and the mixture was dissolved by stirring at room temperature for 4 h. 0.06 mL of glycidyl methacrylate, 0.06 mL of triethylamine and 0.06 g of tetrabutylammonium bromide were added, and the mixture was reacted at 50° C. for 2 h. After cooling to room temperature, the reacted solution was precipitated and washed in acetone, and freeze-dried at -90° C. for 24 h to obtain methacrylated hyaluronic acid.

[0152] S3. Preparation of multimodal deformation sensing hydrogels.

[0153] 0.4 g of methacrylated hyaluronic acid was added to 11 mL of deionized water, and the mixture was dissolved by stirring at room temperature for 1 h. 0.0004 g of N,N-methylenebisacrylamide and 0.0006 g of ammonium persulfate were added, and the mixture was mixed by stirring at room temperature for 10 min. The mixed solution was injected into a mold, and polymerized with 0.5 g of calcium alginate hydrogel under anaerobic conditions at 45 °C for 6 h to obtain a multimodal deformation sensing hydrogel.

[0154] As shown in Table 1, the tensile results show that the multimodal deformation sensing hydrogel prepared in this embodiment has a maximum tensile elongation of 121% and a maximum tensile strength of 1.27 MPa;

[0155] The compression results show that when the multimodal deformation sensing hydrogel prepared in this embodiment is compressed to 70%, the maximum compressive strength reaches 2.9 MPa;

[0156] It shows that the multimodal deformation sensing hydrogel prepared in this example has excellent tensile and compressive mechanical properties;

[0157] As shown in Table 2, the conductivity of the multimodal deformation sensing hydrogel prepared in this example is 0.035 S / cm, indicating that the multimodal deformation sensing hydrogel prepared in this example has excellent conductive properties.

[0158] The multimodal deformation sensing hydrogel prepared by the present invention can sense and identify different movement patterns, and has great application potential in personalized medical care and sports rehabilitation.

[0159] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.

Claims

1. A multimodal deformation sensing hydrogel, characterized in that: The sensing hydrogel comprises the following components in parts by weight: 1-3 parts of alginate hydrogel and 1-3 parts of methacrylated hyaluronic acid; The two long ends of the alginate hydrogel were clamped and dried, and methacrylate hyaluronic acid was dissolved in water and polymerized with the alginate hydrogel to obtain a multimodal deformation sensing hydrogel.

2. A multimodal deformation sensing hydrogel according to claim 1, characterized in that: The alginate hydrogel is placed in air to dry at a temperature of 10 to 40° C. for 3 to 6 hours.

3. The multimodal deformation sensing hydrogel according to claim 1, characterized in that: Methacrylate hyaluronic acid and alginate hydrogel are polymerized under anaerobic and heat-induced conditions, the polymerization temperature is 40-60° C., and the time is 3-6 hours.

4. A method for preparing a multimodal deformation sensing hydrogel according to any one of claims 1 to 3, characterized in that: The method comprises the following steps: S1, adding sodium alginate into water to dissolve to obtain a sodium alginate solution, adding metal ion solution to react to obtain alginate hydrogel, clamping two long ends of the alginate hydrogel, and drying; S2, adding hyaluronic acid into water to dissolve, adding glycidyl methacrylate, triethylamine and tetrabutylammonium bromide to react, and obtaining methacrylate hyaluronic acid; S3. Add methacrylate hyaluronic acid into water to dissolve it, add a cross-linking agent and an initiator to mix, and polymerize with alginate hydrogel to obtain a multimodal deformation sensing hydrogel.

5. The method for preparing a multimodal deformation sensing hydrogel according to claim 4, characterized in that: The mass / volume ratio of sodium alginate to water in step S1 is (1-2 g): (25-30 mL), The metal ion solution is selected from one or more of a calcium chloride solution, a zinc chloride solution, and a barium chloride solution, and the concentration of the metal ion solution is 0.05 to 0.1 g / mL. The volume ratio of the sodium alginate solution to the metal ion solution is (1-2):(1-3).

6. The method for preparing a multimodal deformation sensing hydrogel according to claim 4, characterized in that: The dissolution temperature in step S1 is 10-40°C and the dissolution time is 8-12 hours. The reaction temperature is 10-40°C and the reaction time is 3-6 hours.

7. The method for preparing a multimodal deformation sensing hydrogel according to claim 4, characterized in that: The mass / volume ratio of hyaluronic acid to water in step S2 is (1-3 g):(50-60 mL), The mass / volume ratio of hyaluronic acid, glycidyl methacrylate, triethylamine and tetrabutylammonium bromide is (45-50 g):(1-8 mL):(1-8 mL):(1-8 g).

8. The method for preparing a multimodal deformation sensing hydrogel according to claim 4, characterized in that: The dissolution temperature in step S2 is 10-40°C and the dissolution time is 3-6 hours. The reaction temperature is 40-60°C and the reaction time is 1-4 hours.

9. The method for preparing a multimodal deformation sensing hydrogel according to claim 4, characterized in that: The mass / volume ratio of methacrylate hyaluronic acid to water in step S3 is (0.02-0.04 g): 1 mL, The crosslinking agent is selected from one or more of polyethylene glycol diacrylate, N,N-methylenebisacrylamide, cyclotriene bond, and triallyl isocyanurate; the initiator is selected from one or more of ammonium persulfate, potassium persulfate, 2-hydroxy-2-methylpropiophenone, and α-ketoglutaric acid; the mass ratio of methacrylic hyaluronic acid, crosslinking agent, and initiator is 1:(0.001-0.002):(0.002-0.003); The dissolution temperature is 10-40°C and the dissolution time is 1-2 hours. The mixing temperature is 10-40°C and the mixing time is 10-20 minutes.

10. An application of the multimodal deformation sensing hydrogel according to any one of claims 1 to 3, characterized in that: The sensing hydrogel is applied to wearable flexible sensors.

Citation Information

Patent Citations

  • Preparation method of hydrogel with hierarchical micro-nano structure

    CN110903498A

  • Hydrogel intelligent electronic ligament or tendon

    CN116271218A

  • Macroporous hydrogel with oriented structure as well as preparation method and application of macroporous hydrogel

    CN116769215A

Cited By

  • Multifunctional orchard weeding vegetation blanket based on dynamic response gel

    CN120240213A